IMPROVING THE PROCESS OF TEACHING LITERACY BASED ON GAME TECHNOLOGIES IN PRIMARY GRADES - Mavlonova Mohlaroyim Nurmat kizi (International Journal of Literature and Language Studies, 2026)
This article highlights the role and importance of teaching literacy based on game technologies and interactive methods in increasing the effectiveness of primary school lessons. It is emphasized that the development of independent thinking, creative activity and social skills of students is an important factor in the modern education system. The article reveals the essence of game technologies, methods of their application in the lesson process, and their importance in the formation of students' knowledge, skills and competencies through examples.